Analisa Perhitungan Produksi Alat Berat pada Pelaksanaan Pekerjaan Pembangunan Jalan Usaha Tani Desa Semurut, Kecamatan Tabalar, Kabupaten Berau. - WOJA, SILVESTER (KURVA S JURNAL MAHASISWA, 2012)
Dynamics of Growth and countryside development and also growth of resident and very countryside society economics quickly, claiming the existence of requirement of prasarana and transportation medium which complex progressively and insist on one of them is [is] prasarana walke the. Road-Works of[is Effort Farmer ysng [of] located in Countryside Semurut, Subdistrict Tabalar, Regency Berau represent the very required transportation medium by the masayrakat countryside, utilize to transport the agricultural produce. Refering to above [the] mentioned, governmental Hence Provinsi Kalimantan East [of] [through/ passing] On Duty Public Work, Area Create The Masterpiece, Sub of Rural Growth Planning Area [of] fund allocation have for the road-works of the area, utilize to fulfill the medium requirement walke for society of Countryside Semurut. Along of location which [is] [is] planned to do [by] road-works of[is Effort the Farmer represent the new location representing bog area and growed [by] the coppice, hence require to be [done/conducted] [by] work pengurukan, longly walke + 1,050 km and wide walke 6 m, totally [is] ordinary land;ground hoard volume 15.660 m3, with the distance of location of dig of hoard material ( quarry) with the hoard location + 1 km. In Road-Works execution of[is Effort Farmer of Countryside Semurut, very needed [by] [is] a heavy equipment usage, so that work execution earn as according to goals which have been determined, and use [of] heavy equipment have to be planned well and careful, so that precisely its use, optimal [of] its production and existence of efficiency of equipments expense.